The connectivity frontier - Joan Prats; Juan Andrés Páez (Inter-American Development Bank (IDB), 2018)
The importance of connectivity is growing across the world as the need for access to information and communication technologies is becoming more important for economic development. This paper presents the concept of the connectivity frontier as the expected achievable level of commercially sustainable connectivity for information and communication technologies for each country given the average country's structural and institutional endowments. The connectivity frontier is computed, identifying the key structural and institutional variables that affect connectivity investment in a country. The study uses the connectivity frontier as a benchmark to compare connectivity levels across countries and identify connectivity gaps, illustrating the connectivity gap analysis with an application to Latin American and Caribbean countries. Finally, the paper includes an analysis of the determinants of the connectivity gap using panel data for OECD countries, showing the importance of entry regulation and public ownership to explain the observed connectivity gap.
Keywords: L86; L96; L98; 330; connectivity frontier; economic structure; internet services; institutions; telecommunications